COCONUT PRODUCTION UNDER VARIOUS CROPPING PATTERNS AND ITS CORRELATION TO THE SOIL AND LEAF NUTRIENT ELEMENT - DOAH DEKOK TARIGANS (Pusat Penelitian dan Pengembangan Perkebunan, 2003)
i-ow productivity of coconut farm is the main problem of coconut industry. The fact that intercropped palms were more productive than when solely planted, the most suitable way to increase productivity is through multiple cropping. To cope with (he existing variation of cropping pattern in relation to coconut production, soil and leaf nutrient element, various cropping patterns with four species of perennial crop as intercrops were conducted under study. The objectives of the study were (1) to study the effect of cropping patterns on the growth, nut production and farm productivity of coconut under farmer levels, soil chemical propeties and leaf nutrient element and (2) to study the correlation between growth and production parameter with soil chemical propeties and leaf nutrient elements. Various cropping patens under study namely (1) coconut monoculture (control), (2) coconut + pineapple, (3) coconut + coffee, (4) coconuf - papaya ♦ pineapple, (5) coconut + banana + coffee, and (6) coconut + banana + papaya + coffee i pineapple Total area for each cropping patern was 0.5 ha with coconut planting distance 8 m x 10 m and the palms 35-40 years old The site of the experiment conducted was at Silang, Cavite. Data on coconut growth and production, soil chemical properties and leaf nutrient parameters, were statistically analyzed in a randomized complete block design (RCDB) with three replications. Correlation analysis were performed on the following (1) Growlh and production parameters with soil chemical propeties, and leaf nutrient elements, (2) Relationship among nutrient element in the coconut leaves under various cropping paterns Results of the study showed that the effect of cropping patterns on the number of full-grown nul increased signiicantly more nut and higher amounts of copra per tree were produced in intercropped farms than in the mono-cropped coconut plantation. These increase ranged from 64 to 98 percent in terms of nuts and 70 to 105 percent in terms of copra. Positive correlation was observed between nitrogen in the top soil with weight of copra and nut production. The exchangeable potassium in lop soil was positively correlated with nut production. Meanwhile, the organic mater, content in the soil were positively correlated with weight of copra, nut production but negatively correlated with percentage of nul shedding. These results implies that increase organic matter content in the soil will increase coconut production including fruit set Nitrogen concentration in the leaf was positively and highly signiicantly correlated with number of nut shedding These finding suggested that the increased nitrogen concentration in the leaf greatly promotes nul production and fruit set of the palms under various cropping patterns in coconut The potassium in the leaf was significantly correlated with nul production but negatively correlated with percentage of nut shedding. Key words: Coconut production, cropping patterns, soil chemical, leaf nutrient elements, correlationRINGKASAN Produksi kelapa pada beberapa pola tanam dan hubungannya dengan kandungan unsur hara tanah dan daun kelapaRendahnya produktivitas tanaman merupakan masalah utama pada perkebunan kelapa. Salah satu cara untuk meningkatkan produktivitas yaitu melalui penerapan usahatani kelapa campuran. Suatu kenyataan bahwa penerapan intercropping menyebabkan tanaman kelapa lebih produktif dibandingkan dengan tanaman monokultur. Untuk mengetahu sejauh mana pengaruh tersebut secara ilmiah, serta hubungannya terhadap unsur hara tanah dan unsur hara dalam daun kelapa maka dilakukan penelitian secara terencana pada pertanaman kelapa rakyat produktif. Tujuan penelitian ini (1) untuk mengetahui pengaruh pola tanam terhadap petumbuhan dan produksi tanaman kelapa, terhadap unsur hara dalam tanah dan kadar hara daun kelapa dan (2) mcmpelajari korelasi antara parameter petumbuhan dan produksi kelapa dengan hara tanah serta kadar unsur hara daun. Enam polatanam kelapa yang diuji dalam penelitian ini yaitu (1) kelapa monokultur, (2) pola tanam kelapa + nanas, (3) pola tanam kelapa * kopi, (4) pola tanam kelapa + papaya + nanas , (5) pola tanam kelapa + pisang ♦ kopi dan (6) pola tanam kelapa + pisang + papaya ♦ kopi + nanas dimana masing-masing pola tanam seluas 0.5 ha. Jarak tanam kelapa 8 m x 10 m, dengan umur 40-45 tahun. Penelitian dilakukan di Silang, Cavite. Penelitian menggunakan rancangan acak lengkap (randomized complete block design) dengan tiga ulangan. Parameter yang diamali meliputi jumlah daun, jumlah bunga betina (button) per tandan, kadar unsur hara tanah meliputi kandungan bahan organik, pH, CEC, Nitrogen, Phosphor, Calcium, dan Magnesium. Sedangkan unsur hara daun yaitu Nitrogen, Phosphor, Calsium, dan Magnesium. Analisis korelasi dilakukan terhadap (1) pertumbuhan dan produksi kelapa dengan unsur hara tanah, dan unsur hara daun dan (2) hubungan antar unsur hara daun kelapa pada beberapa polatanam kelapa yang ditclili. Hasil penelitian menunjukkan bahwa produksi buah dan kopra pada polatanam campuran lebih tinggi dibandingkan dengan hasil pola tanam kelapa monokultur. Peningkatan produksi buah 64-98 persen dan kopra 70-105 persen. Kadar nitrogen pada lapisan atas tanah mempunyai korelasi positif dengan berat kopra dan produksi buah. Sedangkan unsur kalium pada lapisan tanah yang sama mempunyai korelasi positif dengan produksi buah kelapa Kandungan bahan organik tanah mempunyai korelasi positif dengan berat kopra, produksi buah namun berkorelasi negatip dengan presentase buah yang gugur (nut shedding) Hasil ini berimplikasi bahwa dengan meningkatnya kadar bahan organik tanah akan meningkatkan produktivitas tanaman kelapa. Lebih lanjut, hasil penelitian menunjukkan bahwa kadar nitrogen dan kalium pada daun mempunyai korelasi positif dengan peningkatan produksi kelapa dan persentasi buah yang jadi.Kata kunci: Produksi kelapa, polatanam, unsur hara tanah, kadar unsur daun, analisis korelasi